Proceedings of the 19th International Symposium on Automation and Robotics in Construction (ISARC) 2002
DOI: 10.22260/isarc2002/0054
|View full text |Cite
|
Sign up to set email alerts
|

Data Interpretation from Leuze RotoScan Sensor for Robot Localisation and Environment Mapping

Abstract: ABSTRACT:Two applications for the use of a laser-scanning device are currently under investigation at Lancaster University. Lancaster University Computerised Intelligent Excavator (LUCIE) is an autonomous excavator which navigates using GPS and compass readings. Work is currently concentrating on navigational safety, for which the rotoscan sensor is employed for obstacle detection, and for possible self-localisation and environment comprehension in ambiguous operational states. Starlifter is a robotic arm buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For monitoring purposes, cameras can be used to provide clear images of the working area. Laser devices can be used in mapping the task area to create three-dimensional images of the workspace (Seward, D., et al, 2002).…”
Section: The Development Processmentioning
confidence: 99%
See 1 more Smart Citation
“…For monitoring purposes, cameras can be used to provide clear images of the working area. Laser devices can be used in mapping the task area to create three-dimensional images of the workspace (Seward, D., et al, 2002).…”
Section: The Development Processmentioning
confidence: 99%
“…This representation is useful in the case of Multi-Input-Multi-Output systems however; it is still applicable to Single-Input-Single-Output (SISO) systems as in the case of the present design of the individual joint control. The PIP approach has several advantages (Taylor, C. J., 2002): It can handle transfer function models of any order The integral of error state has been included to provide inherent integral action The PIP control has a structure which avoids common control system problems The PIP control is robust to pure time delays because it uses control sampling intervals that would be considered quiet coarse by conventional standards It is straight forward to extend it multivariable systems It is possible to use any modern control system design method developed for state-space systems…”
Section: System Controller Designmentioning
confidence: 99%
“…The feasibility analysis results presented in this was in favour of the use of the automated process. Earlier study carried out by Zied et al (2001) on the economic feasibility of the use of Starlifter robotic system in core drilling underneath a motorway bridge showed that the robotic solution is more economic in the short term based on hiring the system. The study was based on cost estimation based on graphical simulation of the proposed system.…”
Section: Summary Of the Model Stepsmentioning
confidence: 99%